JOB SATISFACTION BASED ON THE WORK ENVIRONMENT AND WORK DISCIPLINE AT PT. LOLC VENTURA BSD BRANCH - Ading Sunarto; Asridah Warni Tanjung (International Journal of Multidisciplinary Research and Literature, 2022)
This study aimed to determine the effect of work environment and work discipline on job satisfaction in PT. Lolc Ventura BSD branch, either partially or simultaneously. The method used in this research was quantitative. The sampling technique was carried out using saturated sampling where 105 respondents were obtained. Data analysis was performed using validity test, reliability test, classical assumption test, regression analysis, correlation coefficient analysis, coefficient of determination analysis, and hypothesis testing. The results of this study indicated that work environment had a significant effect on job satisfaction with the regression equation Y = 16,179 + 0,594X1 where the correlation value obtained was 0.421. This value indicated that the two variables had a strong relationship level. The coefficient of determination found was 42.1%. In hypothesis testing, obtained t count > t table or (8.657% > 0.192%). Thus, H0 was rejected and H1 was accepted which indicated a significant effect of work environment on job satisfaction. Work discipline had a significant effect on job satisfaction with the regression equation Y = 15.276 + 0.616X2 and a correlation value of 0.621 which indicated that the two variables had a strong relationship. The value of the coefficient of determination was 38.5%. In hypothesis testing, obtained tarithmetic > ttable or (8.031% > 0.192%) which indicated that H0 was rejected and H2 was accepted. These results indicated that there was a significant effect of work discipline on job satisfaction. Work environment and work discipline had a significant effect on job staisfaction with the regression equation Y = 9.154 + 0.404X1 + 0.375X2. The correlation value of 0.722 showed that the independent variable and the dependent variable had a strong level of relationship. The coefficient of determination obtained was 52.1%, while the remaining 47.9% was influenced by other factors. Hypothesis testing was obtained by the calculated Fvalue > Ftable or (55,443 > 2,690) which indicated that H0 was rejected and H3 was accepted. This means that there is a simultaneous significant effect of work environment and work discipline on job satisfaction in PT. Lolc Ventura BSD branch